Analysis Traditional Market Revitalization For Economic Improvement of Kras Market Kediri - Latif Syaipudin; Idah Nurfajriya Awwalin (SEAN Institute, 2023)
This study explains the problem of the unfavorable image of traditional markets in the eyes of society. special attention from the government for traditional markets, namely through revitalization as a form of market development to become a more organized and attractive location or area for the community. This research uses a qualitative approach with a descriptive type, namely research that prioritizes observing phenomena and requires sharp instincts in making decisions. Data collection techniques with interviews, observation and documentation. The results of this study, are: 1) The impact of the revitalization program on the economic conditions of traders is that it has a good impact on the community, through this revitalization it will remove the impression of a smelly, dirty and dirty traditional market. 2) Constraints and solutions for revitalization programs for merchant sales turnover, namely obstacles related to HR management that are still not qualified to compete with the modern market, the solution for traders must keep up with the times, namely by providing good service and cleanliness.